Beyond the Blackboard: AI-Driven Virtual Tutors and the Evolution of Digital Learning - Amey Dawkhar; Amita Chandekar; Nandini Panchal; Sanket Ghatte (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Traditional learning paradigms have been profoundly altered by the incorporation of Artificial Intelligence (AI) into educational settings. The rise of AI-powered virtual tutors and their effects on the development of digital learning are examined in this paper. We look at the technical underpinnings of virtual tutors, evaluate current applications, and talk about how effective they are in comparison to conventional teaching techniques. We present findings on learner engagement, retention of knowledge, and general satisfaction from a mixed-method study that included surveys and experimental observations. Our results show that while AI-driven tutors improve learning efficiency, accessibility, and personalization, they also present ethical, equity, and data privacy issues. We wrap up by outlining potential avenues for future study to develop AI educational models that are more focused on people.
Keywords: Artificial Intelligence; Virtual Tutors; Digital Learning; Educational Technology; AI in Education